2017
DOI: 10.1111/birt.12273
|View full text |Cite
|
Sign up to set email alerts
|

How do pregnant women use quality measures when choosing their obstetric provider?

Abstract: BackgroundGiven increased public reporting of the wide variation in hospital obstetric quality, we sought to understand how women incorporate quality measures into their selection of an obstetric hospital.MethodsWe surveyed 6141 women through Ovia Pregnancy, an application used by women to track their pregnancy. We used t tests and chi‐square tests to compare response patterns by age, parity, and risk status.ResultsMost respondents (73.2%) emphasized their choice of obstetrician/midwife over their choice of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Studies of clinician selection among pregnant individuals have reported that most of these individuals select their clinician, obstetrician, or midwife and then deliver at whichever hospital or birthing center the clinician has admitting privileges. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Studies of clinician selection among pregnant individuals have reported that most of these individuals select their clinician, obstetrician, or midwife and then deliver at whichever hospital or birthing center the clinician has admitting privileges. 24 …”
Section: Discussionmentioning
confidence: 99%
“…As reported by Declercq et al (2007), the informal channel constituted by friends and relatives is particularly relevant for first-birth mothers. Similarly, both Gourevitch et al (2017) and Gourevitch et al (2019) confirm the weak role played by standard hospital-based quality measures in affecting mothers' preferences. They do observe a strong self-reported interest of mothers in the health of their baby and the quality of the obstetric care they receive, but this is mainly informed through the opinions of peers or relatives.…”
Section: Introductionmentioning
confidence: 86%
“…As reported by Declercq et al (2007), the informal channel constituted by friends and relatives is particularly relevant for first-birth mothers. Similarly, both Gourevitch et al (2017) and Gourevitch et al (2019) confirm the weak role played by standard hospital-based quality measures in affecting mothers' preferences. They do observe a strong self-reported interest of mothers in the health of their baby and the quality of the obstetric care they receive, but this is mainly informed through the opinions of peers or relatives.…”
Section: Introductionmentioning
confidence: 86%